Wear evaluation of palm oil and SAE 15W 40 engine lubricants with a ball-on-disk tester based on an improvised drilling machine - Alfian, D.G.C.; Silitonga, D.J.; Machzumy, F.M.Al; Oktaberi, F.; Triawan, L. (Universitas Mataram, 2023)
This paper introduces a modified ball-on-disk test, utilizing a drilling machine, to investigate the tribological behavior of wear on a plate surface under various lubrication conditions. The tribometer, based on the ball-on-disc principle, employs an improvised bench-top drill press machine. Despite its simplicity, it effectively facilitates wear-track experiments using engine oil (SAE 15W 40) and palm oil as lubricants. Tests are conducted at room temperature, maintaining a constant load at 8.83 N and rotational speed of 180 rpm for 2 minutes per sample. Microscopic analysis of wear scars on the plate samples reveals distinct wear patterns and characteristics for each lubricant, with measurements taken at multiple positions for accuracy. The current work focuses exclusively on wear scar analysis, with findings indicating that engine oil outperforms the counterpart, displaying a smaller wear track width, hence superior lubrication and wear protection capabilities. In contrast, palm oil exhibits a larger wear track, implying limitations in friction reduction and material preservation. This work has demonstrated the practical use of the cost-effective tribometer device for conducting preliminary studies of lubricant wear reduction performance. The test outcomes render valuable insights for lubricant formulators, particularly at the early stage of laboratory-scale development.